2023
DOI: 10.1002/2211-5463.13579
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EZH2 exerts antitumorigenic effects in renal cell carcinoma via LATS1

Abstract: The most common type of kidney cancer in adults is renal cell carcinoma (RCC), which accounts for approximately 90% of cases. RCC is a variant disease with numerous subtypes; the most common subtype is clear cell RCC (ccRCC, 75%), followed by papillary RCC (pRCC, 10%) and chromophobe RCC (chRCC, 5%). To identify a genetic target for all subtypes, we analyzed The Cancer Genome Atlas (TCGA) databases of ccRCC, pRCC, and chromophobe RCC. Enhancer of zeste homolog 2 (EZH2), which encodes a methyltransferase, was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…LATS1 is a key component of the Hippo signalling pathway. When the Hippo signalling pathway is activated, LATS1 induces the degradation of YAP/TAZ, thereby maintaining a state in which the growth and metastasis of cancer cells are inhibited [29]. Deciphering the role of EZH2 in methylation processes sheds light on its potential as a key player in mediating resistance mechanisms and provides valuable insights for targeted therapeutic interventions [30].…”
Section: Methylation Of Tumour Suppressor Genesmentioning
confidence: 99%
“…LATS1 is a key component of the Hippo signalling pathway. When the Hippo signalling pathway is activated, LATS1 induces the degradation of YAP/TAZ, thereby maintaining a state in which the growth and metastasis of cancer cells are inhibited [29]. Deciphering the role of EZH2 in methylation processes sheds light on its potential as a key player in mediating resistance mechanisms and provides valuable insights for targeted therapeutic interventions [30].…”
Section: Methylation Of Tumour Suppressor Genesmentioning
confidence: 99%
“…In HCC, miR-29c-3p directly inhibits DNMT3B, while DNMT3B regulates HCC progression by methylating LATS1. LATS1 has been identified as a tumor suppressor gene, and its inhibition by DNMT3B promotes HCC cell proliferation and migration 75 , 76 . Furthermore, LINC00839 upregulates WTAP to promote liver cancer cell proliferation and invasion through the sponge-like effect of miR-144-3p.…”
Section: Ncrnas To Methylationmentioning
confidence: 99%
“…Moreso, EZH2 has been investigated in relation with sunitinib resistance in mice, the results warranting further studies Frontiers in Cell and Developmental Biology frontiersin.org (Adelaiye-Ogala et al, 2017). A very recent study on ccRCC cell lines showed that inhibition of EZH2 induces anticancer effects through increased apoptosis, reduced invasive and wound healing capacities (Hong et al, 2023). The EZH2 inhibitor used was tazemetostat, which is currently in clinical trials for RCa treatment, among other cancer types (Table 6).…”
Section: Manipulating H3 Methylation Modulators For the Treatment Of Rcamentioning
confidence: 99%